2022
DOI: 10.3390/ijerph191811240
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Influences Affecting Middle-Aged and Elderly Users’ Participation Intention in Health-Related Social Media

Abstract: Social media provide users with multi-directional dialogue for creating and sharing health information that can effectively promote the self-management of health. In regard to the ‘greying’ trend in social media, most researchers have studied the health-related social media (HRSM) acceptance status and use behavior of middle-aged and elderly people, and have explored the role of HRSM in this group. However, the continuous participation of users is the key to the successful operation of HRSM, and is an essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…Their research highlighted the importance of communicating benefits and personal connections over the convenience of using digital devices. Education and raising awareness are therefore essential [34]. Although the COVID-19 pandemic has forced almost the general population to use various digital tools, and older adults were no exception, education and support from other participants in the healthcare system is of crucial importance for this population [7].…”
Section: Discussionmentioning
confidence: 99%
“…Their research highlighted the importance of communicating benefits and personal connections over the convenience of using digital devices. Education and raising awareness are therefore essential [34]. Although the COVID-19 pandemic has forced almost the general population to use various digital tools, and older adults were no exception, education and support from other participants in the healthcare system is of crucial importance for this population [7].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the "gray" trend in social media, most researchers have studied the acceptance status of health-related social media (HRSM) and usage behavior in middle-aged and older people, they explored the role of HRSM in this group. However, the continuous participation of users is the key to the successful operation of HRM and is a prerequisite for the subsequent behavioral habits of HRM of middle-aged and elderly people (Cao et al, 2022). Haghi et al (2017) study aims to explain the role of health websites` visual structure in users' views on their quality and reliability as well as its role in obtaining health information by users.…”
Section: Health Websites and Social Media Platformsmentioning
confidence: 99%
“…In a study on the influence of social networks on health motivation, it was reported that elderly people find the information useful and entertaining, playing an important role in their motivation, directly encouraging them to continue using the tools proposed by physicians 6 . A cross-sectional study including 100 participants aged 60 years or older, recruited from geriatrics clinics of a tertiary care university, reported that the use of mobile phone was of 55% and it was associated 70% of lower probability of having a diagnosis of depression after age, sex, partner status, comorbidities and global cognitive performance (p < 0.005) 7 .…”
Section: Introductionmentioning
confidence: 99%